Werbe Aufmarsch für das Bundes Turn- und Sportfest am 5. und 6. Juli 1930 in Aussig. Serie von 2 Fotos
Werbe Aufmarsch für das Bundes Turn- und Sportfest am 5. und 6. Juli 1930 in Aussig. Serie von 2 Fotos.